Effect of montmorillonite and kaolinite on nitrification in soil - Macura, J; Stotzky, G (Folia microbiologica, 1980)
A soil not naturally containing montmorillonite (M) was amended with approximately 5, 10 or 20% M or kaolinite (K), maintained in a greenhouse under periodic cultivating and alternate wetting and drying of more than two years, and then used in perfusion studies. The incorporation of M enhanced the rate of both heterotrophic degradation of glycine and subsequent autotrophic nitrification in direct relation to the amounts of M added. In soil amended with K, neither degradation nor nitrification was stimulated. The addition of M shortened the lag phase before nitrification was initiated, increased the pH of both the soil and the perfusates, and increased the rate, but not the extent, of oxidation of ammonium to nitrite and nitrate. The addition of CaCO2 or MgCO3, but not of CaSO4, also enhanced the rate of nitrification. The effects observed may have resulted from the influence of M on the pH, buffering capacity, and other soil conditions necessary for maximum activity of nitrifying microorganisms.
Keywords: koncentrace vodíkových iontů; Oxidation-Reduction; kaolin; kvartérní amoniové sloučeniny; Hydrogen-Ion Concentration; Nitrobacter; Glycine; Quaternary Ammonium Compounds; Soil Microbiology; biodegradace; Bentonite; oxidace-redukce; Kaolin; Nitrates; půdní mikrobiologie; Nitrites; dusitany; bentonit; glycin; dusičnany; Biodegradation, Environmental